2015
DOI: 10.1002/elps.201400496
|View full text |Cite
|
Sign up to set email alerts
|

Properties of nucleic acid staining dyes used in gel electrophoresis

Abstract: Nucleic acid staining dyes are used for detecting nucleic acids in electrophoresis gels. Historically, the most common dye used for gel staining is ethidium bromide, however due to its toxicity and mutagenicity other dyes that are safer to the user and the environment are preferred. This Short Communication details the properties of dyes now available and their sensitivity for detection of DNA and their ability to permeate the cell membrane. It was found that GelRed™ was the most sensitive and safest dye to us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
55
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 10 publications
1
55
0
2
Order By: Relevance
“…Ethidium bromide is the most common stain used for nucleic acid detection on electrophoretic gels. This dye emits fluorescence when intercalated into DNA bases of nucleic acids and can interfere in both DNA and RNA synthesis (Singer et al, 1999;Ohta et al, 2001;Martineau et al, 2008;Haines et al, 2015). Ethidium bromide is classified as a strong mutagen and is genotoxic at the typical concentration for gel staining (Schagat and Hendricksen, 2013;Haines et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethidium bromide is the most common stain used for nucleic acid detection on electrophoretic gels. This dye emits fluorescence when intercalated into DNA bases of nucleic acids and can interfere in both DNA and RNA synthesis (Singer et al, 1999;Ohta et al, 2001;Martineau et al, 2008;Haines et al, 2015). Ethidium bromide is classified as a strong mutagen and is genotoxic at the typical concentration for gel staining (Schagat and Hendricksen, 2013;Haines et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…SYBR safe TM , a DNA stain developed by Invitrogen, is classified as non-genotoxic, non-mutagenic, and nonhazardous (Martineau et al, 2008;Evenson et al, 2012). This stain interacts with the DNA grooves instead of intercalating the DNA double stranded (Haines et al, 2015). Moreover, SYBR safe TM can be visualized under a blue light transilluminator, which does not damage the DNA (Martineau et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…DD can penetrate the cell membrane, leading to interactions with genomic DNA (10); however, studies have shown that DD is less mutagenic and genotoxic when compared with EtBr (11). This reduction in toxicity may be due to the different binding mechanism of DD with DNA compared with other intercalating dyes, since DD does not bind between base pairs of DNA but instead binds externally (10). Currently, DD has not been evaluated for use in qPCR applications.…”
mentioning
confidence: 99%
“…Diamond Nucleic Acid Dye (DD) is an external groove binding dye shown to have a similar sensitivity as SG and a limit of detection of 0.5 ng when detecting DNA in agarose gels (10). DD can penetrate the cell membrane, leading to interactions with genomic DNA (10); however, studies have shown that DD is less mutagenic and genotoxic when compared with EtBr (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation